2020
DOI: 10.20411/pai.v5i1.372
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ultraviolet-C Light and a High-Level Disinfection Cabinet for Decontamination of N95 Respirators

Abstract: Background: Shortages of personal protective equipment (PPE) including N95 respirators are an urgent concern in the setting of the global COVID-19 pandemic. Decontamination of PPE could be useful to maintain adequate supplies, but there is uncertainty regarding the efficacy of decontamination technologies.Correction: This is a corrected version of this article. The original version of this article contained data for an additional ultraviolet light device that has been removed from the corrected version as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(158 citation statements)
references
References 23 publications
2
150
0
6
Order By: Relevance
“…25,36 However, an extended cycle with the disinfection cabinet was required to achieve a 6 log 10 reduction in bacteriophage MS2 inoculated on N95 respirators. 18 In the current study, an extended cycle (identified as the optimal disinfection cycle in our experiments) was also required to achieve a 6 log 10 reduction in bacteriophage MS2 or G. stearothermophilus spores on N95 respirators. Similarly, Battelle has reported a prolonged VHP cycle time with a total time of 480 minutes for N95 decontamination.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…25,36 However, an extended cycle with the disinfection cabinet was required to achieve a 6 log 10 reduction in bacteriophage MS2 inoculated on N95 respirators. 18 In the current study, an extended cycle (identified as the optimal disinfection cycle in our experiments) was also required to achieve a 6 log 10 reduction in bacteriophage MS2 or G. stearothermophilus spores on N95 respirators. Similarly, Battelle has reported a prolonged VHP cycle time with a total time of 480 minutes for N95 decontamination.…”
Section: Discussionmentioning
confidence: 87%
“…The test and control respirators were inoculated with ~10 6 colony-forming units (CFU) of G. stearothermophilus spores and ~10 6 plaque-forming units (PFU) of bacteriophage MS2 on the outer and inner surface of the respirator as previously described. 18,25,26 The test organisms were suspended in 8% simulated mucus, 27 and 10 µL aliquots were pipetted onto the respirator surface and spread with a sterile loop to cover an area of 1 cm 2 and allowed to air dry. The test N95 respirators were suspended using metallic 'S' shaped hooks from shelving carts at a height of feet and exposed to PAA submicron droplets.…”
Section: Efficacy Of the Decontamination Process For Treatment Of Conmentioning
confidence: 99%
“…Another benefit of greater UV radiation at high altitude will be possibly higher vitamin D levels, which afford protection against several other viral and bacterial infections by T cell enhancement (Grant et al, 2020). Thus, UV radiation might, theoretically, contribute to slowing the spread of the virus as some groups have suggested (Cadnum et al, 2020;Hamzavi et al, 2020;Keil et al, 2020), but this needs to be examined carefully. However, any action of UV radiation will only be relevant to the outdoor environment and most viral transmission occurs indoors, where people congregate in closer quarters and spend many hours of the day.…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…While different regimens of UVGI and heat treatment are effective against a large number of human pathogens, there is a high degree of variability among the susceptibility to temperature and UVC among microorganisms [ 59 , 120 ]. Thus, while the disinfection procedures reviewed here have focused on SARS-CoV-1 and SARS-CoV-2, they would not necessarily be efficacious against all other pathogens, in particular spore-forming bacteria.…”
Section: Cautionary Notesmentioning
confidence: 99%